1999
DOI: 10.1016/s0008-6363(99)00141-8
|View full text |Cite
|
Sign up to set email alerts
|

Exercise enhances vasorelaxation in experimental obesity associated hypertension

Abstract: These results suggest that the antihypertensive effect of long-term exercise in experimental obesity related hypertension is associated with improved vasodilatation. This is expressed as enhanced relaxation via endogenous and exogenous nitric oxide, and increased endothelial prostacyclin production. The improved control of arterial tone after training could be attributed to the alleviation of hyperlipidemia and insulin resistance, whereas hyperinsulinaemia per se remained unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 32 publications
2
42
1
Order By: Relevance
“…However, we did not find a difference in eNOS-dependent reactivity of cerebral arterioles between sedentary and exercised nondiabetic rats. This finding was surprising given the fact that others have shown that ExT increases the reactivity of peripheral blood vessels (5,11,22,37). However, in a previous study (43), we found that ExT did not influence eNOS-dependent responses of the basilar artery.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…However, we did not find a difference in eNOS-dependent reactivity of cerebral arterioles between sedentary and exercised nondiabetic rats. This finding was surprising given the fact that others have shown that ExT increases the reactivity of peripheral blood vessels (5,11,22,37). However, in a previous study (43), we found that ExT did not influence eNOS-dependent responses of the basilar artery.…”
Section: Discussioncontrasting
confidence: 93%
“…Studies have shown that ExT can improve/ restore responses of peripheral blood vessels during chronic hypertension (5,11,26,33), types 1 and 2 diabetes (23,46,69), and heart failure (30,36). In addition, we have reported that impaired eNOS-dependent responses of the basilar artery observed in rats with type 1 diabetes (T1D) could be restored to that observed in nondiabetic rats by ExT (43).…”
mentioning
confidence: 88%
“…However, a meta-analysis study of exercise in type II diabetic patients showed that exercise failed to decrease blood pressure in this patient subset (64). A longer duration of exercise (14-22 wk) has been shown to reduce systolic blood pressure in these rats using the tail cuff method (4,54). It is possible that the shorter duration of exercise (8 wk) in our study precluded us from observing a decrease in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are confirmed in animal studies. In obese Zucker (fa/fa) rats characterized by moderate hypertension (3,4), hyperlipidemia (5,6), and insulin resistance/impaired glucose tolerance (7,8), exercise improves insulin sensitivity (9) and reduces blood lipids (10), blood pressure (4), and obesity (11,12).…”
mentioning
confidence: 99%